2022
DOI: 10.1002/cbin.11956
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an in vitro model from the vulnerable fish species Coregonus maraena (maraena whitefish): Optimization of growth conditions and characterization of the cell line

Abstract: In this study, a cell line of the fish species Coregonus maraena was produced for the first time. C. maraena is an endangered species, and studies indicate that this fish species will be affected by further population declines due to climate change. This cell line, designated CMAfin1, has been maintained in Leibovitz L‐15 supplemented with 10% fetal bovine serum over 3 years. Both subculturing and storage (short‐term storage at −80°C and long‐term storage in liquid nitrogen) was successful. Cell morphology and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In addition, cell lines should also be established for the fish species of the temperate climate zone, because numerous in vivo experiments are being carried out in "climate research" in particular. Thereby, the production of cell lines from IUCN red-listed fish species should be a priority in order to avoid further reducing these populations through animal testing (Kaya et al 2022). In the last decades, it has been shown that climate change and the associated rising temperatures have a significant impact on fish (e.g.…”
Section: Use Of Fish Cells In Basic Researchmentioning
confidence: 99%
“…In addition, cell lines should also be established for the fish species of the temperate climate zone, because numerous in vivo experiments are being carried out in "climate research" in particular. Thereby, the production of cell lines from IUCN red-listed fish species should be a priority in order to avoid further reducing these populations through animal testing (Kaya et al 2022). In the last decades, it has been shown that climate change and the associated rising temperatures have a significant impact on fish (e.g.…”
Section: Use Of Fish Cells In Basic Researchmentioning
confidence: 99%